Pasarelas de pago al servicio del e-commerce en las empresas de streaming (2022)
With the following monographic work, the collection of bibliographic sources on the conceptualization of electronic commerce, payment gateways and streaming services is sought, specifying the process of an electronic transaction between banks, information on the growth in sales generated by the e-commerce platforms, the first countries that occupy the first places in 2019, and in turn make charts of the growth in sales in the last five years for the Netflix and Amazon Prime streaming companies as the main success stories